Mapas de zonas de risco de epidemias para doenças dos citros no Estado de São Paulo - Lopes, Mariana Viléla [UNESP] (Universidade Estadual Paulista (Unesp), 2007)
O objetivo do presente trabalho foi analisar as condições climáticas do Estado de São Paulo e desenvolver mapas de zonas de risco de epidemias de cancro cítrico, podridão floral e pinta preta do citros. Foram utilizados dados meteorológicos referentes aos anos de 2002, 2003, 2004 e 2005, os quais foram utilizados os modelos de previsão. Para o cancro cítrico desenvolvido por Campbell e Madden (1990) e Hau e Kranz (1990); podridão floral dos citros desenvolvido por Timmer e Zitko (1993) e Timmer e Brown (2000); pinta preta desenvolvido por Hau e Kranz (1990) e Bergamin Filho (1995. Após a contabilização dos índices, foram calculadas as porcentagens de dias favoráveis à ocorrência das doenças durante o ano e em períodos pré-definidos. A partir destas informações, foram gerados os mapas temáticos do Estado de São Paulo, com a distribuição espacial da porcentagem de dias favoráveis à ocorrência das doenças. A região Noroeste do Estado foi a que apresentou a maior porcentagem de dias favoráveis à ocorrência de cancro cítrico. As regiões Sul e Leste foram as que apresentaram maior favorabilidade de ocorrência da podridão floral do s citros. Para a pinta preta a região Sul com pontos no centro do Estado foi a que apresentou maior porcentagem de dias favoráveis a ocorrência da doença.

The objective of the present work was to analyze the climatic conditions of the State of São Paulo and to develop maps of zones of risk of epidemics of citrus canker, postbloom fruit drop of citrus and citrus black spot. They had been used given meteorological referring to the years of 2002, 2003, 2004 and 2005, which had been used the forecast models. For the citrus canker developed by Campbell and Madden (1990) and Hau and Kranz (1990); postbloom fruit drop of citrus developed by Timmer and Zitko (1993) and Timmer and Brown (2000); it citrus black spot developed for Hau and Kranz (1990) and Bergamin Filho (1995). The frequency of the data was hourly and when some station presented imperfection in the series of data, these had been surpassed of the station next. After the accounting of the indices, had been calculated the percentages of days favorable to the occurrence of the diseases in the year and in the periods. From these information, the thematic maps of the State of São Paulo had been generated, with the space distribution of the percentage of days favorable to the occurrence of the diseases. The region the Northwest of the State was the one that presented the biggest percentage of days favorable to the occurrence of citrus canker. The regions South and East had been the ones that had presented greater favorable of occurrence of the postbloom fruit drop of citrus. For the citrus black spot the South region with points in the center of the State was the one that presented greater percentage of favorable days the occurrence of the diseases.
Keywords: Agroclimatic risk indexes; Cítricos - Doenças e pragas; Zoneamento; Xanthomonas axonopodis pv. citri; Colletotrichum acutatum; Guignardia citricarpa